Research Progress of Conjugated Nanomedicine for Cancer Treatment - Bin Zhao; Sa Chen; Ye Hong; Liangliang Jia; Ying Zhou; Xinyu He; Ying Wang; Zhongmin Tian; Zhe Yang; Di Gao (MDPI AG, 2022)
The conventional cancer therapeutic modalities include surgery, chemotherapy and radiotherapy. Although immunotherapy and targeted therapy are also widely used in cancer treatment, chemotherapy remains the cornerstone of tumor treatment. With the rapid development of nanotechnology, nanomedicine is believed to be an emerging field to further improve the efficacy of chemotherapy. Until now, there are more than 17 kinds of nanomedicine for cancer therapy approved globally. Thereinto, conjugated nanomedicine, as an important type of nanomedicine, can not only possess the targeted delivery of chemotherapeutics with great precision but also achieve controlled drug release to avoid adverse effects. Meanwhile, conjugated nanomedicine provides the platform for combining several different therapeutic approaches (chemotherapy, photothermal therapy, photodynamic therapy, thermodynamic therapy, immunotherapy, etc.) with the purpose of achieving synergistic effects during cancer treatment. Therefore, this review focuses on conjugated nanomedicine and its various applications in synergistic chemotherapy. Additionally, the further perspectives and challenges of the conjugated nanomedicine are also addressed, which clarifies the design direction of a new generation of conjugated nanomedicine and facilitates the translation of them from the bench to the bedside.